Cleavage of DNA.RNA hybrids by type II restriction enzymes. - Molloy, P L (1980)
The action of a number of restriction enzymes on DNA.RNA hybrids has been examined using hybrids synthesised with RNAs of cucumber mosaic virus as templates. The enzymes EcoRI, HindII, SalI, MspI, HhaI, AluI, TaqI and HaeIII cleaved the DNA strand of the hybrids (and possible also the RNA strand) into specific fragments. For four of these enzymes, HhaI, AluI, TaqI and HaeIII, comparison of the restriction fragments produced with the known sequences of the viral RNAs confirmed that they were recognising and cleaving the DNA strand of the hybrids at their correct recognition sequences. It is likely that the ability to utilise DNA.RNA hybrids as substrates is a general property of Type II restriction enzymes.